ANALISIS PENGARUH BUDAYA ORGANISASI, KOMPETENSI SDM, MANAJEMEN RISIKO, & INOVASI TEKNOLOGI TERHADAP KUALITAS SISTEM INFORMASI AKUNTANSI MANAJEMEN PADA USAHA MIKRO, KECIL DAN MENENGAH DI SOLO RAYA - Puput Ayu Rukmana; Erma Setiawati (JURNAL ILMIAH EDUNOMIKA, 2026)
The micro, small, and medium enterprise (MSME) sector plays a crucial role in strengthening the country's economic structure, but the majority still face obstacles in implementing high-quality management accounting information systems to support management decision-making processes. This study explores the influence of organizational culture, human resource competency, risk management, and technological innovation on the quality of management accounting information systems in micro, small, and medium enterprises (MSMEs) in the Solo Raya region. A quantitative method was used by collecting primary data from 217 MSME respondents through a questionnaire survey, where participants were determined using a purposive sampling technique. Data processing was carried out using multiple linear regression with the support of statistical applications. The research findings revealed that human resource competency, risk management, and technological innovation have a positive and significant influence on the quality of management accounting information systems, while organizational culture shows a significant negative impact. Additionally, all independent variables simultaneously influence system quality. These findings suggest that strengthening human resource capability, implementing effective risk management, and adopting technological innovation are critical to improving system quality, supporting more informed decision-making, and enhancing the competitiveness of MSMEs. Keywords : Organizational Culture, Human Resource Competency, Risk Management, Technological Innovation, Management Accounting Information Systems, MSMEs